Centralised versus Decentralised Control Reconfiguration for Collaborating Underwater Robots. Issue 21 (2015) - Furno, Lidia; Nielsen, Mikkel Cornelius; Blanke, Mogens
Abstract: The present paper introduces an approach to fault-tolerant reconfiguration for collaborating underwater robots. Fault-tolerant reconfiguration is obtained using the virtual actuator approach, Steffen (2005). The paper investigates properties of a centralised versus a decentralised implementation and assesses the capabilities under communication constraints between the individual robots. In the centralised case, each robot sends information related to its own status to a unique virtual actuator that computes the necessary reconfiguration. In the decentralised case, each robot is equipped with its own virtual actuator that is able to accommodate both local faults and faults within a collaborating unit. The paper discusses how this is done through exploiting structural information (e.g. thruster configuration) for each participant in the cooperation. A test scenario is presented as a case in which an underwater drill needs to be transported and positioned by three collaborating robots as part of an underwater autonomous operation.